Portable Color Recognizer for Color and Vision Deficiency - Mohd Raduan, Ain Farhana; Nabilah Ibrahim; Suhaila Sari (Evolution in Electrical and Electronic Engineering, 2023)
Color blindness is a condition in which a person is unable to recognize similar contrasting colors. Nowadays, color-blind people struggle to recognize the colors of everyday life. This involves activities such as choosing the color of clothes and food, playing sports, gardening, driving a car, and things around them. In addition, blind people also experience the same thing as being unable to see the surrounding environment and even being unable to see and recognize colors. Thus, the purpose of this project is to develop a color recognizer for color-blind people as well as blind people to help them overcome their challenges in daily life. The device uses a TCS3472 color sensor to detect colors, an Arduino Uno to recognize colors, a serial MP3 player speaker to assist color blind people and blind people to hear the names of colors, and a servo motor is to point the colors braille script and provide feedback to the blind people. The device is intended to be user-friendly, portable, and inexpensive. Moreover, the device also works in standalone mode without the need for a PC once it is programmed. Hence, it is found that the proposed device has 75% - 100% accuracy when tested in different locations. In summary, this proposed device has the potential to help those who are color blind and totally blind by assisting them in solving their challenges in recognizing colors in daily life.